Euler’s Formula

Around 1740, the Swiss mathematician, physicist and engineer Leonhard Euler obtained the formula later named after him.\(\require{AMSsymbols}\)

Euler’s Formula

Use the MacLaurin series for cosine and sine, which are known to converge for all real \(x\), and the MacLaurin series for \(\mathrm{e}^x\).

$$\begin{align}
\cos x&=\sum_{n=0}^{\infty}\frac{(-1)^n}{(2n)!}x^{2n}=1-\frac{x^2}{2!}+\frac{x^4}{4!}-\cdots \\
\sin x&=\sum_{n=0}^{\infty}\frac{(-1)^n}{(2n+1)!}x^{2n+1}=x-\frac{x^3}{3!}+\frac{x^5}{5!}-\cdots \\
\mathrm{e}^z &=\sum_{n=0}^{\infty}\frac{z^n}{n!}=1+z+\frac{z^2}{2!}+\frac{z^3}{3!}+\cdots\label{eq:ez}
\end{align}$$

Substitute \(z=j\varphi\) in \(\eqref{eq:ez}\)

$$\begin{align}
\mathrm{e}^{j\varphi}&=\sum_{n=0}^{\infty}\frac{(j\varphi)^n}{n!}=1+j\varphi+\frac{(j\varphi)^2}{2!}+\frac{(j\varphi)^3}{3!}+\cdots
\nonumber\\
&=1+j\varphi-\frac{\varphi^2}{2!}-j\frac{\varphi^3}{3!}+\frac{\varphi^4}{4!}+j\frac{\varphi^5}{5!}-\cdots
\nonumber\\
&=\underbrace{\left(1-\frac{\varphi^2}{2!}+\frac{\varphi^4}{4!}+\cdots\right)}_{\cos\varphi} +j\underbrace{\left(\varphi-\frac{\varphi^3}{3!}+\frac{\varphi^5}{5!}-\cdots\right)}_{\sin\varphi}
\end{align}$$

This leads us to Euler’s formula

$$\shaded{
\mathrm{e}^{j\varphi}=\cos\varphi+j\sin\varphi}$$

Euler’s Identify

For the special case where \(\varphi=\pi\):

$$\mathrm{e}^{j\pi}=\cos\pi+j\sin\pi=-1$$

Rewritten as

$$\shaded{\mathrm{e}^{j\pi}+1=0}$$

This combines many of the fundamental numbers with mathematical beauty

  • The number \(0\), the additive identify
  • The number \(1\), the multiplicative identity
  • The number \(\pi\), the ratio between a circle’s circumference and its diameter
  • The number \(j\), used to find the roots of polynomials defined as \(j=\sqrt{-1}\)
  • The number \(e\), from continuous compounding interest and from \(\frac{\mathrm{d}}{\mathrm{d}x}\mathrm{e}^x=\mathrm{e}^x\)

Cartesian and polar coordinates

Euler’s formula traces out a unit circle in the complex plane as a function of \(\varphi\).  Here, \(\varphi\) is the angle that a line connecting the origin with a point on the unit circle makes with the positive real axis, measured in radians.

Relation between cartesian and polar coordinates (Euler)
Relation between cartesian and polar coordinates

A point in the complex plane can be represented by a complex number written in cartesian coordinates.  Euler’s formula lets you convert between cartesian and polar coordinates.  The polar form simplifies the mathematics when used in multiplication or powers of complex numbers. [wiki]

Any complex number \(z=x+jy\) can be written as

$$
\shaded{
z=x+jy=r(\cos\varphi+j\sin\varphi)=r\,\mathrm{e}^{j\varphi}
}$$

where

$$\begin{aligned}
x&=\Re\{z\} & \mathrm{real\ part\ of\ }z\\
y&=\Im\{z\} & \mathrm{imaginary\ part\ of\ }z\\
r&=|z|=\sqrt{x^2+y^2} & \mathrm{magnitude\ of\ }z\\
\varphi&=\angle z=\mathrm{atan2}(y,x) & \mathrm{angle\ of\ }z
\end{aligned}$$

Another notation method

$$
\shaded{r\,\mathrm{e}^{j\varphi}=\mathrm{e}^{\ln r}\mathrm{e}^{j\varphi}
=\mathrm{e}^{\ln r+j\varphi}}
$$

Relation to trigonometry

Euler’s formula connects analysis with trigonometry.  The connections most easy follow from adding or subtracting Euler’s formulas. [wiki]

$$\left\{
\begin{aligned}
\mathrm{e}^{j\varphi}&=\cos\varphi+j\sin\varphi \\
\mathrm{e}^{-j\varphi}&=\cos(-\varphi)+j\sin(-\varphi)=\cos\varphi-j\sin\varphi
\end{aligned}
\right.$$

Adding gives the \(\cos\varphi\)

$$\left.
\begin{aligned}
\mathrm{e}^{j\varphi}&=\cos\varphi+j\sin\varphi \\
\mathrm{e}^{-j\varphi}&=\cos(-\varphi)+j\sin(-\varphi)=\cos\varphi-j\sin\varphi
\end{aligned}
\right\}
\overset{add}{\Rightarrow}
$$

Addition

$$ \begin{align}
\mathrm{e}^{j\varphi}+\mathrm{e}^{-j\varphi}&=
(\cos\varphi+\cancel{j\sin\varphi}) +
(\cos\varphi-\cancel{j\sin\varphi})\nonumber\\
&=2\cos\varphi
\end{align}\\
$$

So

$$\shaded{
\cos\varphi=\frac{\mathrm{e}^{j\varphi}+\mathrm{e}^{-j\varphi}}{2}}\label{Eulers_sine}$$

Subtracting gives the \(\sin\varphi\)

$$\left.
\begin{align}
\mathrm{e}^{j\varphi}&=\cos\varphi+j\sin\varphi \nonumber\\
\mathrm{e}^{-j\varphi}&=\cos(-\varphi)+j\sin(-\varphi)=\cos\varphi-j\sin\varphi\nonumber
\end{align}
\right\}
\overset{subtract}{\Rightarrow}$$

Subtraction

$$\begin{align}
\mathrm{e}^{j\varphi}-\mathrm{e}^{-j\varphi}&=
(\cancel{\cos\varphi}+j\sin\varphi) –
(\cancel{\cos\varphi}-j\sin\varphi)\nonumber\\
&=2j\sin\varphi
\end{align}$$

Thus

$$\shaded{
\sin\varphi=\frac{\mathrm{e}^{j\varphi}-\mathrm{e}^{-j\varphi}}{2j}}\label{Eulers_cosine}$$

Next

Richard Feynman’s lecture 23 on Algebra provides a clear introduction to complex numbers and \(e^{i\theta}=\cos\theta+i\sin\theta\).

Suggested next reading is Laplace Transforms.

Embedded software developer
Passionately curious and stubbornly persistent. Enjoys to inspire and consult with others to exchange the poetry of logical ideas.

Leave a Reply

Your email address will not be published. Required fields are marked *

 

This site uses Akismet to reduce spam. Learn how your comment data is processed.